2019
DOI: 10.1002/ejoc.201900069
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalytic Asymmetric Michael–Acyl Transfer Reaction of α‐Nitroketones with 2‐Hydroxybenzylidene Ketones

Abstract: An organocatalytic asymmetric cascade Michael–acyl transfer reaction between 2‐hydroxybenzylidene ketones and α‐nitroketones is developed. The 9‐amino(9‐deoxy)‐epi‐hydroquinine catalyst in combination with benzoic acid was found to be the most effective for this reaction and the desired products were isolated in moderate to good yields and excellent enantioselectivities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Consequently, our group developed an organocatalytic asymmetric Michael-acyl transfer reaction of α-nitroketones with unsaturated pyrazolones, 2-hydroxycinnamaldehydes, γ/δ-hydroxyenones, o-quinone methides, etc. [14][15][16][17][18]. Other groups also contributed contemporarily [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, our group developed an organocatalytic asymmetric Michael-acyl transfer reaction of α-nitroketones with unsaturated pyrazolones, 2-hydroxycinnamaldehydes, γ/δ-hydroxyenones, o-quinone methides, etc. [14][15][16][17][18]. Other groups also contributed contemporarily [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…In 2011, three research groups namely Wang, Yan and Kwong independently revealed organocatalytic asymmetric conjugate addition of αnitroketones to β,γ-unsaturated α-keto esters with concomitant acyl transfer reaction to the keto group [11][12][13]. Consequently, our group developed organocatalytic asymmetric Michael-acyl transfer reaction of α-nitroketones with unsaturated pyrazolones, 2-hydroxycinnamaldehydes, γ/δ-hydroxyenones, otrho-quinone methides etc [14][15][16][17][18]. Other groups also contributed contemporarily [19][20][21].…”
Section: Introductionmentioning
confidence: 99%